PENGARUH GOOD CORPORATE GOVERNANCE DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN - Silvia, Nora (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to examine the influence of Good Corporate Governance to the financial performance and Corporate Social Responsibility disclosure to the financial performance. The population is companies which have performed Good Corporate Governance and have performed the Corporate Social Responsibility disclosure in company annual report in Indonesia Stock Exchange during the period of 2010 â 2012. The samples are 11 companies and sample collection technique is using purposive sampling.This research is using secondary data in the form of companyâs annual report which have been obtained from official websites and SWA magazine. Data analysis is performed by using data normality test and classic assumption test which consist of multicolinearity test, heteroscedasticity test, and autocorrelation test. The hypoyhesis test is using multiple linear regressions analysis.The result of research shows that Good Corporate Governance has significant influence to the financial performance and Corporate Social Responsibility disclosure has influence to the financial performance. Each of variable has significant influence to the companyâs financial performance with significance value which has been generated by these variables are less than Î± = 5% level. Keywords: Good Corporate Governance, Corporate Social Responsibility Disclosure, and Financial Performance.